Health care resource utilization patterns among patients with Parkinson's disease psychosis: analysis of Medicare beneficiaries treated with pimavanserin or other-atypical antipsychotics. (31st December 2023) - Rajagopalan, Krithika; Rashid, Nazia; Kumar, Shikhar; Doshi, Dilesh
Abstract: Background: Pimavanserin (PIM) is the only FDA-approved atypical antipsychotic (AAP) for hallucinations and delusions associated with Parkinson's disease psychosis (PDP). Comparative real-world analyses demonstrating its benefits are needed. Objectives: To evaluate health care resource utilization (HCRU) outcomes among PDP patients treated with PIM vs. other-AAPs. Methods: Retrospective cohort analysis of Parts A, B, and D claims from 100% Medicare sample from 01 January 2013–31 December 2019 was conducted. PDP Patients initiating (i.e. index date) continuous monotherapy (PIM vs. other-AAPs) for ≥12-months during 01 January 2014–31 December 2018 without 12-months pre-index AAP use were selected after 1:1 propensity score matching (PSM) on 31 variables (sex, race, region, age, and 27 Elixhauser comorbidities). HCRU outcomes included: annual all-cause and psychiatric hospitalization (short-term stay, long-term stay, and SNF-stay [skilled nursing facility]) rates, annual all-cause and psychiatric-ER visit rates, mean per-patient-per-year (PPPY) hospitalizations, and average length of stay (ALOS). PIM and other-AAPs were compared using generalized linear models (GLM) controlled for demographic characteristics, comorbidities, coexisting-dementia, and coexisting insomnia. Results: Of 12, 164 PDP patients, 48.41% ( n = 5, 889) were female, and mean age was 77 (±8.14) years. Among 1:1 matched patients ( n = 842 in each), 37.8% ( n = 319) on PIM vs. 49.8% ( n = 420) on other-AAPs ( p < .05) reported ≥1 all-cause hospitalizations, respectively. Specifically, short-term and SNF-stay among PIM patients vs. other-AAPs were: 34% ( n = 286) vs. 46.2% ( n = 389) and 20.2% ( n = 170) vs. 31.8% ( n = 267) ( p < .05), respectively. Similarly, 9.6% ( n = 81) of PIM vs. 14.6% ( n = 123) of other-AAPs patients had ≥1 psychiatric hospitalization ( p < .05). Furthermore, ≥1 all-cause and psychiatric ER visit among PIM vs. other-AAPs were 61.6% ( n = 519) vs. 69.4% ( n = 584) and 5.2% ( n = 43) vs. 10.2% ( n = 86) ( p < .05), respectively. PIM also had significantly lower ALOS, and mean PPPY short-term hospitalization and SNF-stays. Conclusions: In this analysis of PDP patients, PIM monotherapy resulted in nearly 12% and 7% lower all-cause hospitalizations and ER visits vs. other-AAPs.